Design and analysis of a GaAs-based 850-nm vertical-cavity surface-emitting laser with different doping in the reflection regions - Mitani, S. M.; Choudhury, P. K.; Alias, M. S. (SPRINGER, 2007)
The present paper deals with the analysis of a non-oxide type of vertical-cavity surface-emitting laser (VCSEL) for operation at 850 nm. The modeling and characterization of the VCSEL is presented in the context of design considerations. Efforts are made to emphasize the behavioral features of the proposed VCSEL, in view of the analytical investigation, which has been performed through a series of simulations for various relevant parameters that are vital for the determination of the VCSEL characteristics. Some of these parameters are the intensity and refractive-index distributions, gain response, spontaneous emission, material gain variations, etc. The results obtained are compared with the oxide-confined VCSEL. It is observed that the proposed model of the VCSEL is suitable at the operating wavelength of 850 nm.